Successful surgical treatment of left main coronary stenosis with CABG and cardiac resynchronization therapy in a patient after the modified Bentall procedure: A case report - Kono, Tetsuya; Tsukioka, Katsuaki; Matsumura, Yu; Naito, Kazuki; Takano, Tomohiro (SAGE open medical case reports, 2024)
We present a case of an 82-year-old woman who developed sustained heart failure with left ventricular dyssynchrony after the modified Bentall procedure. Persistent circulatory instability and complete atrioventricular block suggested coronary artery stenosis. Multidetector computed tomography revealed stenosis of the grafted portion of the coronary artery. The patient was successfully treated by coronary artery bypass grafting with simultaneous epicardial cardiac resynchronization therapy system implantation.